Motor adaptation capacity as a function of age in carrying out a repetitive assembly task at imposed work paces. (October 2017) - Gilles, Martine Annie; Guélin, Jean-Charles; Desbrosses, Kévin; Wild, Pascal
Abstract: The working population is getting older. Workers must adapt to changing conditions to respond to the efforts required by the tasks they have to perform. In this laboratory-based study, we investigated the capacities of motor adaptation as a function of age and work pace. Two phases were identified in the task performed: a collection phase, involving dominant use of the lower limbs; and an assembly phase, involving bi-manual motor skills. Results showed that senior workers were mainly limited during the collection phase, whereas they had less difficulty completing the assembly phase. However, senior workers did increase the vertical force applied while assembling parts, whatever the work pace. In younger and middle-aged subjects, vertical force was increased only for the faster pace. Older workers could adapt to perform repetitive tasks under different time constraints, but adaptation required greater effort than for younger workers. These results point towards a higher risk of developing musculoskeletal disorders among seniors. Highlights: Aging and work pace are two factors affecting workers' motor adaptations used to perform the required work. All three age groups of workers were able to adapt their output to the two imposed work paces. Motor adaptation was more difficult to achieve for older workers when movement involved more the lower limbs in the task.